Anatomical Variants of Post-ganglionic Fibers within the Pterygopalatine Fossa: Implications for Endonasal Skull Base Surgery - Li, Lifeng; London, Nyall R., Jr.; Prevedello, Daniel M.; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives The vidian nerve provides parasympathetic innervation to the nasal cavity and the lacrimal gland. Previous anatomic studies have primarily focused on preservation or severance of the vidian nerve proximal to the pterygopalatine ganglion (PPG). This study aimed to assess its neural fibers within the pterygopalatine fossa after synapsing at the PPG, and to explore potential clinical implications for endoscopic endonasal skull base surgery.Methods An endonasal transpterygoid approach was performed on eight cadaveric specimens (16 sides). The PPG and maxillary nerve within the pterygopalatine fossa were divided. The vidian nerve was traced retrograde into the foramen lacerum, and postganglionic fibers distal to the PPG were dissected following the zygomatic nerve into the orbit. Potential communicating branches between the ophthalmic nerve (V1) and the PPG were also explored.Results All sides showed a plexus of neural communications between the PPG and the maxillary nerve. The zygomatic nerve exits the maxillary nerve close to the foramen rotundum, piercing the orbitalis muscle to enter the orbit in all sides. The zygomatic nerve was identified running beneath the inferior rectus muscle toward a lateral direction. In 7/16 sides (43.75%), a connecting branch between V1 and the pterygopalatine ganglion was observed.Conclusion Neural communications between the PPG and the maxillary nerve were present in all specimens. A neural branch from V1 to the PPG potentially contributes additional postganglionic parasympathetic function to the lacrimal gland.
Keywords: vidian nerve; pterygopalatine ganglion; postganglionic fiber; foramen lacerum; orbit